AdS/CFT duality involving deformed PP-waves from the Lunin-Maldacena background - Smolic, Milena (My University, 2008)
ABSTRACT WOULD NOT LOAD ON DSpace
Keywords: string theory; AdS/CFT correspondence; Lunin-Maldacena background; PP-wave limit